Sex-related differences in clothing-microclimate and subjective perceptions while wearing two outdoor jackets during submaximal exercise in a cool environment. Issue 9 (2nd September 2019) - Wenger, Sebastian; Wright, Tom; Bechtold, Thomas; Nachbauer, Werner
Abstract: This study aimed to identify sex-related differences in clothing-microclimate and subjective perceptions while wearing two outdoor jackets in a setting that is representative for outdoor sports at a leisure level. Ten male and 10 female subjects were testing a thin one-layer jacket and a wind- and waterproof three-layer membrane jacket in a climatic chamber (12 °C, 40% relative humidity) during rest, exercise and recovery. Relative humidity, temperature and sweat residues in the clothing system, perceptions of comfort and physiological parameters were measured. For females, relative humidity, sweat residues and loss of body mass were significantly lower without significantly influencing perceptions of comfort. It can be concluded that sex has a strong effect on clothing-microclimate in outdoor jackets with drier microclimate for females. Furthermore, our findings suggest that females are more sensitive to humidity within the clothing system and that they cool easier, especially in periods of rest.